Habitual Sleep Measures are Associated with Overall Body Fat, and not Specifically with Visceral Fat, in Men and Women. Issue 10 (1st October 2018) - Dekker, Sigrid A.; Noordam, Raymond; Biermasz, Nienke R; de Roos, Albert; Lamb, Hildo J.; Rosendaal, Frits R.; Rensen, Patrick C.N.; van Heemst, Diana; de Mutsert, Renée
Abstract : Objective: This study aimed to investigate the associations of sleep duration and sleep quality with visceral adipose tissue (VAT) in middle‐aged individuals. Methods: In this cross‐sectional analysis of baseline measurements of the Netherlands Epidemiology of Obesity (NEO) study, participants underwent anthropometry and completed the Pittsburgh Sleep Quality Index (PSQI) for assessing short sleep duration (as sex‐specific age‐adjusted percentiles) and poor quality (PSQI > 5). VAT was assessed by magnetic resonance imaging in a random subgroup. We performed linear regression analyses to examine associations of short sleep and poor sleep with measures of body fat, adjusted for confounding, including total body fat in models with VAT. Results: A total of 5, 094 participants (52% women; mean age of 56 [SD 6] years), 1, 947 of whom had VAT measurements, were analyzed. The difference in VAT between poor sleep (PSQI > 5) and good sleep (PSQI ≤ 5) was 7.2cm 2 (95% CI: 1.2‐13.8) in women and 16.1cm 2 (95% CI: 6.2‐26.0) in men. These differences attenuated toward the null after the adjustment for total body fat. Similar patterns of associations were observed for short sleep (lowest 10% compared with median 60%). Conclusions: Our results suggest that measures of sleep are not specifically associated with a higher amount of VAT.